Applied Legal Hermeneutics in 18th-Century Fes: Al-Tāwudī’s Treatise on the Effect of Long Duration in bayʿ al-thunyā Transactions - Oberauer, Norbert (Islamic law and society, 2025)
The present study is an analysis of a treatise (risāla) by the 18th-century Mālikī al-Tāwudī in which he discusses a doctrinal detail regarding bayʿ al-thunyā, a common stratagem to circumvent the prohibition of interest. I use al-Tāwudī’s text as a lens to reconstruct the hermeneutical perspective of a Muslim jurist of the late premodern era. In the first section, I show that al-Tāwudī’s legal reasoning is strongly informed by the legacy of Mālikī discourse on bayʿ al-thunya, which is one of constant disagreement over the acceptability of the institution. In the course of this conflict, various doctrinal compromises were negotiated, only to be challenged again by the invention of new stratagems or by rigorist backlashes. Al-Tāwudī’s treatise must be understood as part of this doctrinal tug of war.